Pelatihan Power Point Sebagai Bahan Ajar Berbasis Game Sederhana Bagi Anggota Gabungan Organisasi Penyelenggara Taman Kanak-Kanak Indonesia (GOPTKI) Kota Yogyakarta - Amir Hamzah (Jurnal Pengabdian kepada Masyarakat Radisi, 2022)
Kindergarten teachers' ability to master various information technologies for learning today is required absolutely. One of the important skills is to package teaching materials in the form of simple games, because kindergarten-age children really like games. Power Point is an application from Microsoft that can be applied  to design teaching materials in the form of simple games.  Training to improve the ability of kindergarten teachers in this application area has been held.  This training was held with participants from the Association of Indonesian Kindergarten Organizing Organizations (GOPTKI) in Yogyakarta City.  The target of this activity is to improve the ability of kindergarten teachers to package interesting teaching materials using the Power Point application. The method used is the lecture method, a simple game-making demo and game-making practice. The evaluation was carried out using a post-training questionnaire. The results of the evaluation show that this activity is very useful for teachers in preparing interesting teaching materials. Participants 86.4% were satisfied and 89% answered that the training was in accordance with the needs of the community.